Financial literacy and fintech adoption among millennials in Metro Manila, Philippines: An analysis - Toh, Alyanna Marie L. (Animo Repository, 2023)
This study delves into the intricate role of financial literacy in shaping the adoption of financial technology (fintech) among millennials in Metro Manila, Philippines. Despite the global upsurge in fintech usage, the relationship between financial literacy and fintech adoption in the Philippines remains inadequately explored. This research endeavors to bridge this gap by shedding light on the level of financial literacy and the extent of fintech adoption among millennials in the region. By conducting a comprehensive analysis of data from 207 survey participants, this study examines the influence of various factors, including perceived benefits, perceived ease of use, perceived risk, trust, and demographic attributes, on fintech adoption. Notably, the findings highlight the mediating role of financial literacy in the relationship between perceived risk and fintech adoption. The results indicate that enhanced financial literacy can mitigate the impact of perceived risk on fintech adoption. However, no significant mediation by financial literacy was observed in the relationships between fintech adoption and other factors. These insights contribute to the advancement of our comprehension regarding the dynamics of fintech adoption and lay the groundwork for future research and practical strategies aimed at promoting financial inclusion through technology.